Using ethnography in implementation research to improve nutrition interventions in populations - Tumilowicz, Alison (Matern Child Nutr, 2016)
‘Implementation research in nutrition’ is an emerging area of study aimed at building evidence‐based knowledge and sound theory to design and implement programs that will effectively deliver nutrition interventions. This paper describes some of the basic features of ethnography and illustrates its applications in components of the implementation process. We review the central purpose of ethnography, which is to obtain the emic view – the insider's perspective – and how ethnography has historically interfaced with nutrition. We present examples of ethnographic studies in relation to an analytic framework of the implementation process, situating them with respect to landscape analysis, formative research, process evaluation and impact evaluation. These examples, conducted in various parts of the world by different investigators, demonstrate how ethnography provided important, often essential, insights that influenced programming decisions or explained programme outcomes. Key messages. Designing, implementing and evaluating interventions requires knowledge about the populations and communities in which interventions are situated, including knowledge from the ‘emic’ (insider's) perspective. Obtaining emic perspectives and analysing them in relation to cultural, economic and structural features of social organisation in societies is a central purpose of ethnography. Ethnography is an essential aspect of implementation research in nutrition, as it provides important insights for making decisions about appropriate interventions and delivery platforms; determining how best to fit aspects of programme design and implementation into different environmental and cultural contexts; opening the ‘black box’ in interventions to understand how delivery and utilisation processes affect programme outcomes or impacts; and understanding how programme impacts were achieved, or not.